The Impact of Co-Creation with Customers on Service Innovation in the Moroccan Context - Yousfi Aouad; Sahar Aboueljaouad (International Journal of Engineering and Management Research, 2019)
In recent years, innovation has become the foolproof weapon of companies to hold competitive advantages. However, innovation in services remains misunderstood, due in particular to the intangible aspect of services. The aim of this research is to shed more light on the elements of service innovation, through an analysis by the concept of “co-creation” with clients, and the impact of the latter on service innovation in the Moroccan context.